Time-restricted feeding protects against septic liver injury by reshaping gut microbiota and metabolite 3-hydroxybutyrate - Jing-Juan Hu; Fan Deng; Qi-Shun Sun; Qing-Ming Xiong; Yue Min; Si-Yuan Feng; Ze-Bin Lin; Peng-Han Chen; Zhen Hu; Ling Wu; Xiao-Feng Chen; Sun Xie; et al. (Gut Microbes)
Liver injury is an independent risk factor for multiple organ dysfunction and high mortality in patients with sepsis. However, the pathological mechanisms and therapeutic strategies for sepsis-associated liver injury have not been fully elucidated. Time-restricted feeding (TRF) is a promising dietary regime, but its role in septic liver injury remains unknown. Using 16S rRNA gene sequencing, Q200 targeted metabolomics, transcriptomics, germ-free mice, Hmgcs2/Lpin1 gene knockout mice, and Aml12 cells experiments, we revealed that TRF can mitigate septic liver injury by modulating the gut microbiota, particularly by increasing Lactobacillus murinus (L. murinus) abundance, which was significantly reduced in septic mice. Further study revealed that live L. murinus could markedly elevate serum levels of metabolite 3-hydroxybutyrate (3-HB) and alleviate sepsis-related injury, while the knockout of the key enzyme for 3-HB synthesis (3-hydroxy-3-methylglutaryl-CoA synthase 2, Hmgcs2) in the liver negated this protective effect. Additionally, serum 3-HB levels were significantly positively correlated with L. murinus abundance and negatively correlated with liver injury indicators in septic patients, demonstrating a strong predictive value for septic liver injury (AUC = 0.8429). Mechanistically, 3-HB significantly inhibited hepatocyte ferroptosis by activating the PI3K/AKT/mTOR/LPIN1 pathway, reducing ACSL4, MDA, LPO, and Fe2+ levels. This study demonstrates that TRF reduces septic liver injury by modulating gut microbiota to increase L. murinus, which elevates 3-HB to activate PI3K/AKT/mTOR/LPIN1 and inhibit hepatocyte ferroptosis. Overall, this study elucidates the protective mechanism of TRF against septic liver injury and identifies 3-HB as a potential therapeutic target and predictive biomarker, thereby providing new insights into the clinical management and diagnosis of septic liver injury.